A prática pedagógica de professores de alunos com transtorno de déficit de atenção/hiperativadade - Andrade, Maria da Conceição de Oliveira (2006)
This study is inserted at the Line of Strategical Research of Thinking and Knowledge production which scientific projects about the relation of thinking and knowledge production are realized. The accomplishment of this dissertation involved an empiric research at a school of the municipal district of Natal RN. Our purpose was to investigate the practice of the staff working with students who present Disabilities and Attention Deficit Hyperactivity (DADH) at regular classes due to the organization of thinking in pedagogical strategies. The object of this study is presented at the center of the questions which involves the conscious analysis of the problems and needs that emerge at the school. Considering the specialty of the theme, we choose a methodology whose focus is the dialogue and the sharing of meanings with the partners of this research through the observation of the activities developed at class/school and interviews/conversations with six teachers of first and second cycles of primary education. According with the study, some theoretician presumptions of Mr. Freire (2001), Mr. Nóvoa (1995), Mr. Bohm (2005) and son on. The results reveled at the research indicate the fragility of a continuous formation directed to the development of critical-reflexive thinking of the teachers.The teachers revel conceptions due to formation, pedagogical practices and the relation with the parents and coordinators, through their performances and speeches, allowing us to identify some pedagogical strategies used. We identified some negative response about the process of learning-developing of these pedagogical strategies such as the one we call unconcern . The strategy of sitting the student at the front row chairs can have positive and negative responses depending on the way the teacher act and follow the student. Other strategies identified as positive response bringers at the learning-developing process and that should be reinforced by the staff are the playful and the group assignments . At this perspective, the school needs to develop a collective project between the pedagogical team and teachers to overcome the needs of all students, and as a consequence, of the staff and improve the positive strategies, minimizing the negative ones and allowing the organizations of new strategies that promotes the improvement of learning-teaching process of the students with DADH